2005
DOI: 10.1038/sj.onc.1209011
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic regulation of telomerase gene expression by transcriptional and post-transcriptional mechanisms

Abstract: Basal telomerase activity is dependent on expression of the hTERT and hTR genes and upregulation of telomerase gene expression is associated with tumour development. It is therefore possible that signal transduction pathways involved in tumour development and features of the tumour environment itself may influence telomerase gene regulation. The majority of solid tumours contain regions of hypoxia and it has recently been demonstrated that hypoxia can increase telomerase activity by mechanisms that are still p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
69
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 32 publications
3
69
1
2
Order By: Relevance
“…(a) Koshiji et al observed that hypoxia-induced HIF-1a significantly inhibited hTERT expression in human colon cancer cells, in sharp contrast to other reports (11). (b) Different mechanisms, including transcriptional and post-transcriptional approaches, have been implicated in hypoxia-regulated hTERT expression (10,(12)(13)(14)16). It remains to be defined whether these regulatory pathways contribute to the enhanced hTERT expression or telomerase activity in all human cancer cells.…”
Section: Introductioncontrasting
confidence: 41%
See 1 more Smart Citation
“…(a) Koshiji et al observed that hypoxia-induced HIF-1a significantly inhibited hTERT expression in human colon cancer cells, in sharp contrast to other reports (11). (b) Different mechanisms, including transcriptional and post-transcriptional approaches, have been implicated in hypoxia-regulated hTERT expression (10,(12)(13)(14)16). It remains to be defined whether these regulatory pathways contribute to the enhanced hTERT expression or telomerase activity in all human cancer cells.…”
Section: Introductioncontrasting
confidence: 41%
“…By promoting angiogenesis, HIF-1 plays important roles in progression, invasiveness, or metastasis of malignant diseases (7,8). Furthermore, recent studies have suggested that hypoxic treatment or overexpression of HIF-1a affects hTERT and telomerase expression (10)(11)(12)(13)(14)(15)(16). Most observations showed that the incubation of human cancer cells at lower levels of oxygen enhanced hTERT mRNA expression and telomerase activity via HIF-1a -mediated trans-activation of the hTERT gene.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of hTERT, it has been demonstrated that the transcriptional complex containing RNA polymerase II, TFIIB, HIF, and coactivators recruits at the promoter under hypoxia and remains associated with the gene as long as transcription proceeds. This induces a switch in the splice pattern in favour of an active form of the enzyme (Anderson et al, 2006). A similar mechanism might operate during the transcription of the CA9 gene.…”
Section: Discussionmentioning
confidence: 96%
“…This fact might suggest a differential cooperation of the transcriptional apparatus with the components of the splicing machinery in the processing of the CA9 transcript depending on the physiological circumstances. Indeed, there are several examples of the splicing events regulated by hypoxia such as those related to hTERT, TrkA, and XBP1 (Romero-Ramirez et al, 2004;Taconelli et al, 2004;Anderson et al, 2006). In the case of hTERT, it has been demonstrated that the transcriptional complex containing RNA polymerase II, TFIIB, HIF, and coactivators recruits at the promoter under hypoxia and remains associated with the gene as long as transcription proceeds.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the ribonucleoprotein complex telomerase is reliant on the expression of both hTR and hTERT genes, the regulation of which is tightly coordinated on multiple levels by transcriptional, post-transcriptional (Zhao et al, 2000(Zhao et al, , 2005Cong et al, 2002;Anderson et al, 2006;Bilsland et al, 2006) and epigenetic mechanisms (Atkinson et al, 2005;Serakinci et al, 2006). In most normal somatic cells, telomerase is inactivated following development so that telomeres shorten after each round of replication until they reach a critical length, signalling senescence or cell death.…”
mentioning
confidence: 99%